Raltegravir for HIV-1 infected children and adolescents: efficacy, safety, and pharmacokinetics - Larson KB; King JR; Acosta EP (Dove Medical Press, 2013)
Kajal B Larson, Jennifer R King, Edward P Acosta Department of Pharmacology and Toxicology, University of Alabama at Birmingham, Birmingham, AL, USA Abstract: Raltegravir was the first HIV integrase strand-transfer inhibitor to be approved by the US FDA, in October 2007, for the treatment of HIV-1 infection in combination with other antiretroviral agents. Raltegravir can be used in treatment-naïve and -experienced patients, as well as for the treatment of multidrug-resistant infection. Raltegravir exists in two formulations: a film-coated tablet administered orally at 400 mg twice daily, and a chewable tablet administered orally at 300 mg twice daily. In 2011, raltegravir was also approved for the treatment of children and adolescents, ages 2–18 years. For adolescents (ages 12–18 years), the recommended dose is 400 mg twice daily (film-coated tablet). If children (ages 6–12 years) weigh at least 25 kg, the film-coated tablet is recommended at 400 mg twice daily. Otherwise, patients receive the chewable tablet according to weight-based dosing at approximately 6 mg/kg/dose. Studies are ongoing for children ages 4 weeks to 2 years, and preliminary efficacy and safety data are promising. This article reviews current studies on the efficacy, safety, and pharmacokinetics of raltegravir in the pediatric population and the challenges of treating HIV in children and adolescents. Keywords: raltegravir, pediatrics, pharmacokinetics, safety, efficacy